A Computationally Inexpensive Battery Model for the Microscopic Simulation of Electric Vehicles - Schellenberg, Sebastian; Berndt, Rüdiger; Eckhoff, David; German, Reinhard (80th IEEE Vehicular Technology Conference Fall (VTC 2014-Fall), 2014)
The transition from classic combustion engine vehicles to electric vehicles is a major step to reduce worldwide CO2 emissions. In order to correctly and efficiently investigate impacts on the electric grid and the dimensioning of charging infrastructure, or to explore new technologies for a further increase of the driving range, realistic simulation models are required. In this paper, we present an accurate yet computationally inexpensive battery and kinematic model to be used in microscopic traffic simulation to help study the performance of thousands of electric vehicles. Our model also supports recuperation and range extender modules while only relying on the vehicle's speed and a set of constant predefined parameters. It can therefore be easily coupled with current sophisticated traffic simulators. We show its applicability and correctness regarding the State of Charge and power flows using comprehensive real-life experiments.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.acompu
Keywords: Electromobility; IVC; lithium-ion battery model

A Lightweight Simulation Framework for the Analysis of Electrified Vehicle Fleets - Berndt, Rüdiger; Schellenberg, Sebastian; Eckhoff, David; German, Reinhard (81th IEEE Vehicular Technology Conference Spring (VTC 2015-Spring), 2015)
Replacing combustion vehicles with electric vehicles is a major step towards reducing CO 2 emissions. With regard to this shift, in particular commercial or governmental vehicle fleets are believed to be early adopters. However, the electrification of vehicle fleets is a complex task since it can have a huge impact on companies’ day-to-day-business. This article presents a lightweight simulation framework to support the planning process and to study important effects of vehicle fleet electrification. Our discrete event-based approach allows to investigate economical and environmental aspects, such as the impact on operating costs, the required electric energy, or the amount of CO 2 emissions. Based on a given trip schedule (consisting of start time, distance, and duration), the framework allows deriving all necessary information, among others to dimension both the vehicle fleet and the charging infrastructure. We show the usefulness and the capability of our model by presenting results for a mid-sized company’s vehicle fleet comprising 100 vehicles.
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD7.alight
Keywords: Electromobility; Discrete Event-based Simulation

A stochastic V2V LOS/NLOS model using neural networks for hardware-in-the-loop testing - Stadler, Christina; Flamm, Xenia; Gruber, Thomas; Djanatliev, Anatoli; German, Reinhard; Eckhoff, David (Proceedings of the 2017 IEEE Vehicular Networking Conference (VNC), 2017)
Many of the envisioned applications based on Vehicle-to-Vehicle (V2V) communication require a certain amount of information received from other road users. Urban scenarios pose a particular challenge to the communication quality for Vehicular Ad-Hoc Networks (VANETs) as obstacles such as buildings, foliage, and infrastructure attenuate the signal. These challenges have to be taken into account already at the development stage of applications. In this paper we introduce a wall-clock time test approach which is capable of emulating the availability of information depending on the topology of an urban scenario. To this end, we make use of a neural network to predict LOS/NLOS probabilities which can then in turn be used to predict packet success rates. Our method achieves a high prediction accuracy that enables the realistic testing of a device-under-test in terms of communication and computational loa
UnivIS-Import:2018-09-06:Pub.2017.tech.IMMD.IMMD7.astoch
Keywords: Buildings; Computational modeling; Emulation; Neural networks; Receivers; Topology; Vehicular ad hoc networks

Evaluating the Electrification of Vehicle Fleets Using the Veins Framework - Schellenberg, Sebastian; Berndt, Rüdiger; German, Reinhard; Eckhoff, David (Proceedings of the 1st OMNeT++ Community Summit 2014, 2014)
The simulative performance evaluation of future Intelligent Transport Systems (ITSs) is a challenging task. New mobility patterns, induced by car sharing or autonomous vehicles, the switch towards electric or hydrogen vehicles, and the communication between vehicles (and infrastructure) are believed to change road traffic as we know it. Investigating new applications and protocols, or finding answers to strategic questions—like the optimal placement of charging infrastructure—is often done by means of simulation. The biggest challenge is the development of realistic models that are required for these simulations in order to produce meaningful results. The case study discussed in this paper involves a company maintaining a vehicle fleet of one hundred vehicles. In this article we will discuss how we extend and deploy the Veins framework, which couples OMNeT++ and SUMO, to help in the process of electrifying this vehicle fleet, i.e., replacing combustion engine cars with electric vehicles to save money and lower CO 2 emissions.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.evalua_5
Keywords: E-Mobility; Simulation; IVC

Exploring GLOSA systems in the field: Technical evaluation and results - Stahlmann, Rainer; Möller, Malte; Brauer, Alexej; German, Reinhard; Eckhoff, David (Computer Communications, 2018)
UnivIS-Import:2018-09-05:Pub.2018.tech.IMMD.IMMD7.explor
Keywords: DRIVE C2X; EAD; ESC; Evaluation; Field trial; GLOSA

GLOSA for Adaptive Traffic Lights: Methods and Evaluation - Bodenheimer, Robert; Eckhoff, David; German, Reinhard (9th International Workshop on Communication Technologies for Vehicles (Nets4Cars-2015-Fall), 2015)
UnivIS-Import:2015-11-17:Pub.2015.tech.IMMD.IMMD7.glosaf

How Electric Vehicles Can Benefit from Vehicular Networking - Schellenberg, Sebastian; Berndt, Rüdiger; Eckhoff, David; German, Reinhard (3rd GI/ITG KuVS Fachgespräch Inter-Vehicle Communication (FG-IVC 2013), 2015)
Wireless exchange of information between vehicles or vehicles and infrastructure nodes is believed to both improve traffic safety and traffic efficiency. Another trend that can currently be observed is a growing market share of electric vehicles. Unfortunately, electric vehicles still suffer from limited driving ranges and long charging times. In this paper, we not only show possible applications to alleviate these problems by the help of wireless communication but also point to models and tools necessary for their evaluation. We especially discuss how – when a vehicle is aware of its surroundings and able to predict the behavior of other vehicles or traffic lights – it can potentially optimize the process of recuperation, that is, the charging of the battery when braking. Furthermore, we show that vehicular communication can be beneficial to optimize charging strategies or job dispatching in vehicle fleets.
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD7.howele
Keywords: Electromobility; Vehicular Communication; Discrete-Event Simulation

Modeling Country-Scale Electricity Demand Profiles - Pruckner, Marco; Eckhoff, David; German, Reinhard (Winter Simulation Conference (WSC '14), 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.modeli_2

Multi-hop for GLOSA systems: Evaluation and results from a field experiment - Stahlmann, Rainer; Tomatis, Andrea; German, Reinhard; Eckhoff, David (2017 IEEE Vehicular Networking Conference (VNC), 2017)
UnivIS-Import:2018-02-22:Pub.2017.tech.IMMD.IMMD7.multih

On the Impact of Antenna Patterns on VANET Simulation - Eckhoff, David; Brummer, Alexander; Sommer, Christoph (Proceedings of the 8th IEEE Vehicular Networking Conference (VNC 2016), 2016)
Although the level of realism in vehicular network simulation is constantly increasing, antenna radiation patterns have only rarely entered the picture. In this paper we investigate the impact of these antenna patterns on the outcome of a city-wide simulation with hundreds of cars as well as an isolated intersection collision avoidance scenario. We show that in both cases pronounced differences can be observed: Compared to idealistic isotropic antennas, using realistic antennas changes the distribution of angle of arrival, affecting network topology dynamics. In collision avoidance applications, the antenna radiation pattern can make the difference between a crash and a successful emergency brake, strongly indicating that antenna characteristics should find more consideration in vehicular network simulatio
UnivIS-Import:2017-01-09:Pub.2016.tech.IMMD.IMMD7.onthei
Keywords: to-appear

Proceedings of the 5th GI/ITG KuVS Fachgespräch Inter-Vehicle Communication (FG-IVC 2017) - Djanatliev, Anatoli; Hielscher, Kai-Steffen; Sommer, Christoph; Eckhoff, David; German, Reinhard (2017)
Inter-vehicle communication (IVC), the management and control of network connections among vehicles as well as between vehicles and existing network infrastructure, is a maturing research field that is gaining a massive momentum. First standardization efforts across all layers, by both IEEE and ETSI, have already borne fruit, allowing researchers to gain valuable insights into both the strengths and the shortcomings of current approaches. The U.S. Department of Transportation decided to introduce IVC until 2020 using IEEE 802.11p, while in Europe the decision is not met yet. The investment of European automobile manufacturers and OEMs into this idea is not only expressed in successful efforts to reserve dedicated radio spectrum harmonized across Europe, but is also reflected in numerous research ventures in cooperation with academia. However, the gathered knowledge is still fragmented, making it hard for new players to get into the game and affording even experienced groups only a restricted view on this complex field. Furthermore, new research questions concerning technologies and services arise in current time. In particular, a more general view on connected mobility is addressed where not only vehicles, but also pedestrians, bikers, and bicyclists are considered in connected contexts. On this basis new innovations and services can be generated that are using appropriate technologies and conjointly aim to improve the future mobility. <br

Spatial and Temporal Charging Infrastructure Planning Using Discrete Event Simulation - Pruckner, Marco; German, Reinhard; Eckhoff, David (2017 Annual ACM Conference on SIGSIM Principles of Advanced Discrete Simulation (SIGSIM-PADS '17), 2017)
UnivIS-Import:2017-07-10:Pub.2017.tech.IMMD.IMMD7.spatia
Keywords: Charging infrastructure planning; Charging stations; Discrete event simulation; Electric vehicles; Electromobility

Technical Evaluation of GLOSA Systems and Results From the Field - Stahlmann, Rainer; Möller, Malte; Brauer, Alexej; German, Reinhard; Eckhoff, David (8th IEEE Vehicular Networking Conference (VNC 2016), 2016)
The goal of Green Light Optimal Speed Advisory (GLOSA) systems is to lower CO2 emissions and to avoid unnecessary stopping in intersection approach scenarios by giving speed advices to drivers based on current and future traffic light signal phase timings. These systems have been widely evaluated by means of simulation and, while most research focuses on the impact assessment of GLOSA along with environmental influences, minor attention was drawn to the holistic technical evaluation of included sub-modules and implementations. In this paper we address this problem with a novel and holistic concept for the technical evaluation of IEEE 802.11p based GLOSA systems. We introduce metrics to cover the whole spectrum of GLOSA operations and identify important factors that are usually not considered in simulations, yet, strongly influencing the results. We demonstrate how this concept is used to evaluate the real-world GLOSA system tested in the European Commission co-funded field trial DRIVE C2X. Results derived from Field Operational Test (FOT) data show that our metrics are well-suited to assess the performance of the GLOSA system, but also to identify sources of potential problems or bottlenecks. Based on our findings, we argue that most simulation studies are too optimistic and that further considerations are required to deploy real-world GLOSA systems.
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD7.techni
Keywords: GLOSA; DRIVE C2X; Field Trial; Evaluation

Towards the City-scale Simulation and Performance Assessment of Electric Vehicles - Masalkina, Ekaterina; Eckhoff, David; Berndt, Rüdiger; German, Reinhard (2nd GI/ITG KuVS Fachgespräch Inter-Vehicle Communication (FG-IVC 2014), 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.toward
Keywords: non-peer

Veins: The Open Source Vehicular Network Simulation Framework - Sommer, Christoph; Eckhoff, David; Brummer, Alexander; Buse, Dominik S.; Hagenauer, Florian; Joerer, Stefan; Segata, Michele (Recent Advances in Network Simulation, 2019)
We describe Veins, an open-source model library for (and a toolbox around) OMNeT++, which supports researchers conducting simulations involving communicating road vehicles—either as the main focus of a study or as a component. Veins already includes a full stack of simulation models for investigating cars and infrastructure communicating via IEEE 802.11 based technologies in simulations of Vehicular Ad Hoc Networks (VANETs) and Intelligent Transportation Systems (ITS). Thanks to its modularity, though, it can equally well be used as the basis for modeling other mobile nodes (like bikes or pedestrians) and communication technologies (from mobile broadband to visible light). Serving as the basis for hundreds of publications and university courses since its beginnings in the year 2006, today Veins is both one of the most mature and established tools in this domain. In this chapter, we give a brief overview of recent developments regarding the architecture, simulation models, and supporting code of Veins; we also present two practical use cases, discuss two extensions, and conclude with a brief discussion of using Veins as a virtual appliance. The framework, code examples, and tutorial simulations can be downloaded from http://veins.car2x.org</a